(3KeQI ebGdI aj GdQhGFMs - (3YHO Gddg Hf GdWjH GdHZOGOj , nCoHh GdnanQL GHf GdpqWpqjH , J (B435 (3g` s
(3ChdgG (B:s
(3GdYdI ai Cf GdCTjGA GdWjHI GdQGFMI EPG JHNQ GdEfSGf HgG cGfJ QGFMJgG ef HYO CcKQ efgG ef bQH s
(3BNQgG (B:s
(3hGdOgf GdPi dGjJZjQ ef GdYQb cOgf GdhQO aEf gPG EPG NGdW GdYQb dGjJZjQ efg , hCeKGd gPg EPG Odc GdHOjf HgG SNfJ hCaQW YdjgG HGddjS hJZjQJ JeJ KeQI GdebGdI ai GdQhGFM s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3GdfSNI HgG MhGTs
(3fSNI fajSI LOkGs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(888/3) s
Keywords: (3GdadSaI hGdefWbs